Uji Adaptasi Somaklonal Kentang (Solanum tuberosum L.) Kultivar Introduksi - Nurhayati Ansori Mattjik; Slamet Muharmoko (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
One of The Asian Vegetable Research and Development Center programs is to get superior varieties potato. The experiment was objected to study somaclonal variety of several introduced potato varieties in order to select superior varieties from them. The plant height, the number of node, and petiole length of Atlantic cultivar were significant different from somaclonal cultivars, even though the number of stem and internode length were not different. However the number and weight of tuber Red Pontiac, Desiree, Russet Burbank, and Eba significant different from those somaclonal cultivars, but not the Atlantic cultivar. According to the principal component analysis for seven quantitative variables of the 34 plants numbers, there were two principal variables. The both variables I.e. variable 1 and 2, were able to explain about 79.3 % of the total variation. Therefore using the first and second variables may be explained the most of data variation. Somaclonal variation induced by irradiation were able to improve morfologis characters and yield, especially for Atlantic cultivar. Each of Atlantic and Red Pontiac somaclonal cultivar number had far relationship with their mother plants. Key words: Somaclonal, Potato